A Review of Leadership Qualities among Building Refurbishment Project Managers - Yacob, Ridzuan; Saruwono, Masran; Ismail, Zulhabri (International Journal of Engineering and Technology, 2018)
This paper provides a review of potential leadership qualities among building refurbishment project managers. The scope of work in refurbishment projects is very much different to that of new building projects. The key features associated with refurbishment projects are that they are unique, risky, highly complex, and inherently filled with uncertainties that are constant throughout the project’s lifecycle. Furthermore, these projects have always been identified with poor project performance that encompasses time, cost, and quality aspects. Despite the greater attention received in recent years, most previous research that provided solutions for the poor performance issues had narrowly focused on technical measures instead of human impact elements. Consequently, leadership qualities amongst project managers were not examined. This study aims to identify potential leadership qualities among building refurbishment project managers. In addition, the relationships between uncertainty factors and performance of refurbishment projects as mediated by the leadership qualities will also be determined. To achieve this aim, a literature search was conducted and relevant articles reviewed from 1997 to 2017. Initially, 125 articles were identified. However, only 70 articles remained after the second stage of the screening process. Arising from this review, a research model was proposed. This model serves as the basis for extended research on leadership qualities among project managers to better manage uncertainties in refurbishment projects.
Keywords: Building refurbishment project; uncertainty factors; leadership qualities; project manager; project performance